Lost scriptures : books that did not make it into the New Testament - Ehrman, Bart D.; ebrary, Inc. (New York : Oxford University Press, 2003)
"We may think of the twenty-seven books of the New Testament as the only sacred writings of the early Christians, but this is not at all the case. Lost Scriptures offers an anthology of up-to-date and readable translations of many non-canonical writings from the first centuries after Christ - texts that have been for the most part lost or neglected for almost two millennia." "Lost Scriptures gives readers a vivid picture of the range of beliefs that battled each other in the first centuries of the Christian era. It is an essential resource for anyone interested in the Bible or the early Church."--BOOK JACKET.
Non-Canonical Gospels -- Non-Canonical Acts of the Apostles -- Non-Canonical Epistles and Related Writings -- Non-Canonical Apocalypses and Revelatory Treatises -- Canonical Lists.
Includes bibliographical references.
Keywords: Apocryphal books (New Testament)